2023
DOI: 10.3390/catal13040642
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Magnesium Oxide Nanoparticles and Nanocomposites for Photocatalytic Antimicrobial, Antibiofilm and Antifungal Applications

Abstract: Magnesium oxide nanoparticles (MgO NPs) have emerged as potential materials for various biomedical applications due to their unique physicochemical properties, including biodegradability, biocompatibility, cationic capacity, high stability and redox properties. MgO NPs have become an attractive platform to combat microbes and may be a promising alternative to overcome challenges associated with eliminating microbial biofilms and antibiotic resistance. Hence, due to the increasing use of MgO NPs in biomedicine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(18 citation statements)
references
References 163 publications
1
17
0
Order By: Relevance
“…Nanotrace elements and their biosynthesis have gained widespread attention recently due to the advent of nanotechnology. Nanotrace elements have demonstrated encouraging outcomes in poultry diets. Studies have indicated that nanoparticles of critical minerals including calcium, zinc, copper, selenium, and chromium have been examined for their potential advantages in growth performance, feed consumption, and the health condition of animals .…”
Section: Introductionmentioning
confidence: 99%
“…Nanotrace elements and their biosynthesis have gained widespread attention recently due to the advent of nanotechnology. Nanotrace elements have demonstrated encouraging outcomes in poultry diets. Studies have indicated that nanoparticles of critical minerals including calcium, zinc, copper, selenium, and chromium have been examined for their potential advantages in growth performance, feed consumption, and the health condition of animals .…”
Section: Introductionmentioning
confidence: 99%
“…And the emergence of multidrug‐resistant (MDR) superbugs makes conventional antibiotics ineffective, further exacerbating this threat [2] . Nowadays, many studies began to construct artificial enzymes, [3] peptide sequences [4] and nanomaterials [5] to eliminate bacteria. Nanomaterials may induce antimicrobial effects against bacteria by several modes‐of‐action, including physical direct interaction of extremely sharp edges of nanomaterials with cell wall membrane; [6] ROS generation [7] even in dark; [8] trapping the cells within the aggregated nanomaterials; oxidative stress; [9] interruption in the glycolysis process of the cells; [10] DNA damaging; [11] metal ion release; [12] contribution in generation/explosion of nanobubbles [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of magnesium oxide nanoparticles (MgO NPs) is increasingly recognized in many industrial and commercial applications owing to its unique physicochemical characteristics, including minimal toxicity, cationic capability, resisting corrosion, dielectric behavior, optical clarity, superior stability, and redox potential. 6 Recently, MgO NPs have attracted significant attention in medical applications due to their remarkable biocompatibility and bioresorbable nature. 6 The presence of magnesium ions, which are an essential component of human biology, further enhances their appeal.…”
Section: Introductionmentioning
confidence: 99%
“…By using environmentally acceptable, nontoxic, and economically advantageous one-step production techniques, the biomolecules and phytochemicals that occur in plant extracts induce the reduction of metal ions into nanosized particles. The utilization of magnesium oxide nanoparticles (MgO NPs) is increasingly recognized in many industrial and commercial applications owing to its unique physicochemical characteristics, including minimal toxicity, cationic capability, resisting corrosion, dielectric behavior, optical clarity, superior stability, and redox potential . Recently, MgO NPs have attracted significant attention in medical applications due to their remarkable biocompatibility and bioresorbable nature .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation